Global Mobility Report 2017 : Tracking Sector Performance - Sustainable Mobility for All (Washington, DC, 2017)
The Global Mobility Report 2017 (GMR) is the first-ever attempt to examine performance of the transport sector globally, and its capacity to support the mobility of goods and people, in a sustainable way. The GMR is built around three components: (i) four global objectives that define “sustainable mobility”; (ii) quantitative and qualitative targets for those objectives, drawn from international agreements; and (iii) indicators to track country-level progress towards those objectives. It covers all modes of transport, including road, air, waterborne and rail.